2021
DOI: 10.1002/hipo.23403
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adropin on learning and memory in rats tested in the Morris water maze

Abstract: Adropin is a secreted peptide, which is composed of 43 amino acids and shows an effective role in regulating energy metabolism and insulin resistance. Motor coordination and locomotor activity were improved by adropin in the cerebellum. However, it is not known whether adropin administration has an effect on spatial learning and memory. In this study, we investigated the effect of adropin on spatial learning and memory and characterized the biochemical properties of adropin in the hippocampus. Thirty male Spra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…131,132 Ozkan et al (2022) comprehensively explored the neuroprotective effect of adropin participating in the Akt/CREB/brain-derived neurotrophic factor (BDNF) signaling pathway using the Morris water maze, Y-maze, and object location recognition tests. 133 Wang et al (2013) found that intraventricular injection of the neuroprotective peptide humanin in mice could reduce Beclin-1-positive cells in hippocampal CA1, CA3, and DG by immunofluorescence detection. 134 Considering all of this evidence, it can be seen that the combination of chemical analysis, molecular docking, cells, and animal models has become a common method to evaluate the efficacy of food-derived peptides in the treatment of AD.…”
Section: Efficacy Evaluation Methods Of Food-derived Peptides In Ad T...mentioning
confidence: 99%
See 1 more Smart Citation
“…131,132 Ozkan et al (2022) comprehensively explored the neuroprotective effect of adropin participating in the Akt/CREB/brain-derived neurotrophic factor (BDNF) signaling pathway using the Morris water maze, Y-maze, and object location recognition tests. 133 Wang et al (2013) found that intraventricular injection of the neuroprotective peptide humanin in mice could reduce Beclin-1-positive cells in hippocampal CA1, CA3, and DG by immunofluorescence detection. 134 Considering all of this evidence, it can be seen that the combination of chemical analysis, molecular docking, cells, and animal models has become a common method to evaluate the efficacy of food-derived peptides in the treatment of AD.…”
Section: Efficacy Evaluation Methods Of Food-derived Peptides In Ad T...mentioning
confidence: 99%
“…131,132 Ozkan et al (2022) comprehensively explored the neuroprotective effect of adropin participating in the Akt/CREB/brain-derived neurotrophic factor (BDNF) signaling pathway using the Morris water maze, Y-maze, and object location recognition tests. 133 Wang et al (2013) found that intraventricular injection of the neuroprotective peptide humanin in mice could reduce Beclin-1-positive cells in hippocampal CA1, CA3, and DG by immunofluorescence detection. 134…”
Section: Efficacy Evaluation Methods Of Food-derived Peptides In Ad T...mentioning
confidence: 99%
“…MWM test was used to measure hippocampus-dependent cognitive function as previously described ( 25 ). All behavioral tests were performed during the active period of the photoperiod.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, a study utilizing insulin-resistant hepatocytes showed that adropin could reduce glucose production in the liver. Adropin treatment downregulated the transcription of hepatic gluconeogenesis genes by inhibiting the binding site of transcription factors forkhead box protein O1(FoxO1) and cAMP-response element binding protein (CREB), along with their co-activators, peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC1α) and CREB regulated transcription coactivator 2 (CRTC2), respectively, to the promoter of gluconeogenesis genes [ 47 , 66 ]. FoxO1-PGC1α and CREB-CRTC2 complex promoter binding is required to activate the transcription of genes that are involved in hepatic glucose production [ 67 , 68 ].…”
Section: The Role Of Adropin In Health and Diseasementioning
confidence: 99%
“…Interestingly, this effect of adropin was not observed in insulin-sensitive hepatocytes [ 66 ]. This research team earlier reported that a downregulation in adropin expression led to systemic insulin resistance in mice that were introduced to a high-fat diet for a long period [ 16 ].…”
Section: The Role Of Adropin In Health and Diseasementioning
confidence: 99%